2020
DOI: 10.14201/eks.19112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Digital Competences in Communication Students across four Latin American Universities

Abstract: Professional skills deemed necessary to work in the field of Communication in Latin America have shifted due to the ever more pressing necessities regarding Information and Communication Technologies. This study analyzes the cases of 4 different academic programs in Communications, belonging to 4 universities in the region (Argentina, Colombia, Peru, and Venezuela), comparing their students in 3 phases of their formation (first semester, fourth semester, eight or last semester). We employed questionnaires for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
5
0
5
Order By: Relevance
“…This conclusion should be contrasted in a subsequent study to assess whether the perceptions expressed by teachers correspond to their objective digital competence or whether, on the contrary, there really is environmental conditioning that influences the self-concept of digital competence. On the other hand, the professors’ levels of digital competence are like those expressed by students in the Latin American and Caribbean areas [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion should be contrasted in a subsequent study to assess whether the perceptions expressed by teachers correspond to their objective digital competence or whether, on the contrary, there really is environmental conditioning that influences the self-concept of digital competence. On the other hand, the professors’ levels of digital competence are like those expressed by students in the Latin American and Caribbean areas [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research shows that students cope better with basic tasks describing digital competences than with more difficult tasks, where the level of their competences is rather low [34]. The obtained results are important not only at the level of shaping an appropriate education strategy, but also at the stage of finding a suitable job [35,36] by people graduating from schools and universities.…”
Section: Discussionmentioning
confidence: 59%
“…In several research it was also found that men had higher levels of digital competence than women (He & Milliner 2014;Crawford-Visbal et al, 2020). The results obtained by Esteve-Mon and colleagues (2020) show that digital competence is closely related to digital problem-solving (computational thinking), that is, students with higher digital competence scores had also higher digital problem -solving competency.…”
Section: Discussionmentioning
confidence: 95%